Inter- and intra-team variability in game patterns: A narrative review - Martins, J. B.; Afonso, J.; Mendes, A.; Santos, L.; Mesquita, I. (Revista Portuguesa de Ciências do Desporto, 2021)
The purpose of this narrative review was to evaluate the game patterns variability in team sports, that is, how game patterns differ across and within different performance levels. We synthesized match analysis-derived knowledge addressing variability in game patterns and conceptually organized the findings into an umbrella framework to help researchers better situate future investigations and highlight gaps that should be addressed by the literature. We structured the study of game pattern variability under five dimensions: (a) inter-team variability based on sex/gender; (b) inter-team variability due to competitive level; (c) inter-team variability within the same competitive level; (d) inter- and intra-team variability due to positional status; and (e) intra-team variability within the same positional status. Relevant gender-based differences in game patterns are identified, but researchers often publish data on men and women separately, inhibiting more direct comparisons. Game pattern variability is present across different competitive levels and, more interestingly, also within the same competitive level, allowing different performance models to coexist at the highest levels of competition. There is variability emerging from the different positional status of the players, but also intra-team variability within the same positional status. Overall, the study of game patterns variability can be divided into (at least) five different, but complementary dimensions, each affording valuable knowledge to improve coaches` understanding of the game dynamics.